Determinan terhadap Niat Membayar Wakaf Uang - Mudrikah, Siti (el Buhuth: Borneo Journal of Islamic Studies, 2021)
Abstract Cash Waqf is one of the familiar points that are predicted to be able to provide an alternative to poverty and welfare problems for Indonesia by seeing its great potential. This study aims to determine the reasons why someone intends to pay cash waqf among members of IPNU-IPPNU Centtral Java, who in fact are adolescents and educated, meaning that here the respondent are not people who have not received education. This study uses quantitative methods with purposive sampling. The Questionare was filled in by 100 respondents but only 99 respondents are valid who are members of IPNU-IPPNU in Central Java, the data analysis method uses Structural Equation Modelling (SEM) PLS then the data is processed using the Smart PLS application. The results showed that the subjective norm and Emotional Experience variabels had a positive effect on the intention to pay cash waqf. Meanwhile, Attitude, Perceptions of Behavior Control, and Peer Influences have no effect on the intention to pay cash waqf for IPNU-IPPNU members in Central Java. Keywords: Cash Waqf, TPB Theory, Emotional Experience, Peer Influences. Abstrak Wakaf uang menjadi salah satu point primadona yang digadang mampu memberikan alternatif permasalahan kemiskinan dan kesejahteraan bagi Indonesia dengan melihat potensi yang besar. Penelitian ini bertujuan untuk mengetahui alasan seseorang berniat untuk membayar wakaf uang di kalangan anggota IPNU/IPPNU Jawa Tengah yang notabenya mereka adalah usia remaja (usia 19-24 tahun) dan terpelajar artinya disini respondennya bukan orang yang tidak mengenyam pendidikan. Penelitian ini menggunakan metode kuantitatif dengan purposive sampling. Kuesioner di isi oleh 100 orang responden namun yang valid hanya 99 responden yang tergabung dalam anggota IPNU/IPPNU di Jawa Tengah, metode analisis data menggunakan Structural Equation Modelling (SEM) PLS kemudian data diolah menggunakan aplikasi Smart PLS. Hasil penelitian menunjukkan untuk variabel norma subjektif dan Emotional Experience berpengaruh positif terhadap niat membayar wakaf uang. Sedangkan Sikap, Persepsi Kontrol Perilaku, dan Peer Influences tidak berpengaruh terhadap niat membayar wakaf uang bagi anggota IPNU/IPPNU di Jawa Tengah. Kata Kunci: wakaf uang, Teori TPB, Emotional Experience, Peer Influences.